Honeycomb structure
Patent Information
- Application Number
- CN202580016472.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-08
- Filing Date
- 2025-03-06
- Publication Date
- 2026-10-09
AI Technical Summary
不过,关于这些载体,气体流通时的压力损失较高,CO2的吸附工艺中需要较大的能量,因此,正在探讨将蜂窝结构体用作载体(例如专利文献1)
[0064]根据本发明,可提供能够确保强度且使温室效应气体的吸附量增大的蜂窝结构体。
Smart Images

Figure CN122892731A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to honeycomb structures. Background Technology
[0002] To combat global warming, the demand for technologies that recover and utilize greenhouse gases (such as carbon dioxide) from the atmosphere and exhaust gases is increasing. For example, as a representative carbon dioxide (CO2) recovery technology, technologies for adsorbing CO2 from the atmosphere (DAC: Direct Air Capture) are being developed. DACs include several types, such as liquid absorption, membrane separation, and solid adsorption. In solid adsorption, the CO2 adsorption (absorption) material is typically supported on a substrate. As the substrate used in solid adsorption, high specific surface area is required, so granular, sheet-like, and fiber-like carriers are the mainstream. However, these carriers suffer from high pressure loss during gas flow, and the CO2 adsorption process requires significant energy. Therefore, the use of honeycomb structures as carriers is being explored (e.g., Patent Document 1).
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Publication No. 2018-538137 Summary of the Invention
[0006] Honeycomb structures are primarily manufactured through extrusion molding, but due to factors such as their own weight, the size that can be manufactured to the designed dimensions is limited. Therefore, in order to ultimately obtain a honeycomb structure of the size used in devices for recovering greenhouse gases such as CO2, a columnar honeycomb structure of the desired size is formed by bonding the sides (outer peripheral walls) of multiple smaller columnar honeycomb structures (hereinafter, columnar honeycomb units) together. However, this columnar honeycomb structure has the following problem: since greenhouse gases do not flow between the sides, the sides cannot be effectively utilized for the adsorption of greenhouse gases.
[0007] The present invention was carried out to solve the problems described above, and its object is to provide a honeycomb structure that can ensure strength and increase the adsorption of greenhouse gases.
[0008] The inventors of this invention have conducted in-depth research on the structure of columnar honeycomb cells used in greenhouse gas recovery devices, and as a result, discovered that by making the sides of the columnar honeycomb cells contact each other in a manner that satisfies specific conditions, the aforementioned problems can be solved, thus completing this invention. Specifically, this invention is illustrated below.
[0009] [1] A honeycomb structure comprising multiple columnar honeycomb units containing an adsorbent material capable of adsorbing greenhouse gases.
[0010] The honeycomb structure is characterized in that...
[0011] The columnar honeycomb units are arranged such that their sides face each other, and at least a portion of the facing sides are in direct or indirect contact.
[0012] The contact portion occupies 0.6% to 92.0% of one of the said sides.
[0013] The lengths of the contact portions in the axial direction and in the direction orthogonal to the axial direction of the columnar honeycomb unit are both more than 2% of the length of the side edge.
[0014] [2] The honeycomb structure according to [1] is characterized in that,
[0015] At least a portion of the opposite sides are in contact with each other through a pad.
[0016] [3] The honeycomb structure according to [2] is characterized in that,
[0017] The thickness of the liner is 0.2 to 10.0 mm.
[0018] [4] The honeycomb structure according to any one of [1] to [3] is characterized in that,
[0019] The length of the contact portion of the columnar honeycomb unit in the direction orthogonal to the axial direction is less than 90% of the length of the side edge.
[0020] [5] The honeycomb structure according to [4] is characterized in that,
[0021] The contact portion is located at the end and / or center of the side edge of the columnar honeycomb unit in a direction orthogonal to the axial direction.
[0022] [6] The honeycomb structure according to any one of [1] to [5] is characterized in that,
[0023] The length of the contact portion along the axial direction of the columnar honeycomb unit is less than 30% of the length of the side edge.
[0024] [7] The honeycomb structure according to [6] is characterized in that,
[0025] The contact portion is located at the end and / or center of the side edge of the columnar honeycomb cell along the axial direction.
[0026] [8] The honeycomb structure according to any one of [1] to [7] is characterized in that,
[0027] A slit is provided on the opposite side.
[0028] [9] The honeycomb structure according to [8] is characterized in that,
[0029] At least a portion of the slit is disposed on the side surface that does not overlap with the contact portion.
[0030] The depth of the slit is less than 50% of the length between the side with which the slit is formed and the side opposite to the side with which the slit is formed.
[0031] The slit occupies less than 20% of one of the sides, and,
[0032] The combined proportion of the contact portion and the slit on one of the sides is less than 100%.
[0033]
[10] The structure according to [9] is characterized in that,
[0034] The maximum width of the slit is less than 50 mm.
[0035]
[11] The honeycomb structure according to any one of [1] to
[10] is characterized in that,
[0036] The columnar honeycomb unit has an outer peripheral wall and a partition wall, the partition wall being disposed on the inner side of the outer peripheral wall and dividing it into multiple compartments extending from a first end face to a second end face.
[0037]
[12] The honeycomb structure according to
[11] is characterized in that,
[0038] The total pore volume of the outer peripheral wall and the partition wall is 0.2–1.5 cm. 3 / g.
[0039]
[13] The honeycomb structure according to
[11] or
[12] is characterized in that,
[0040] The average pore size of the outer peripheral wall and the partition wall is 0.1 to 15.0 μm.
[0041]
[14] The honeycomb structure according to any one of
[11] to
[13] is characterized in that,
[0042] The thickness of the outer peripheral wall is 0.1 to 4.0 mm.
[0043]
[15] The honeycomb structure according to any one of
[11] to
[14] is characterized in that,
[0044] The outer peripheral wall and the partition wall have the same thickness.
[0045]
[16] The honeycomb structure according to any one of
[11] to
[15] is characterized in that,
[0046] The outer peripheral wall and the partition wall are made of a material containing the adsorbent material.
[0047]
[17] The honeycomb structure according to any one of
[11] to
[15] is characterized in that,
[0048] The adsorbent material is supported on the surface of the outer peripheral wall and the partition wall.
[0049]
[18] The honeycomb structure according to any one of [1] to
[17] is characterized in that,
[0050] The content of the adsorbent material in the columnar honeycomb unit is 30-96% by mass.
[0051]
[19] The honeycomb structure according to any one of [2] to
[18] is characterized in that,
[0052] The gasket has adhesive properties.
[0053]
[20] The honeycomb structure according to any one of [2] to
[19] is characterized in that,
[0054] The liner is made of a material containing components capable of adsorbing greenhouse gases.
[0055]
[21] The honeycomb structure according to any one of [2] to
[20] is characterized in that,
[0056] The liner is made of a material that requires a load of less than 2000 kPa to compress 80%.
[0057]
[22] The honeycomb structure according to any one of [2] to
[21] is characterized in that,
[0058] The pad is disposed in the cell structure such that when the thickness in the uncompressed state not disposed in the cell structure is set as a, and the thickness in the compressed state disposed in the cell structure is set as b, a / b is greater than 1.0 and less than 20.0.
[0059]
[23] The honeycomb structure according to any one of [2] to
[22] is characterized in that,
[0060] The liner is made of a material whose residual compressive strain is less than 10% after being compressed 80% from its uncompressed state (not configured in the honeycomb structure) and held for 24 hours, followed by a 30-minute interval.
[0061]
[24] The honeycomb structure according to any one of [2] to
[23] is characterized in that,
[0062] The heat resistance temperature of the gasket is above 100°C.
[0063] Invention Effects
[0064] According to the present invention, a honeycomb structure can be provided that ensures strength and increases the adsorption of greenhouse gases. Attached Figure Description
[0065] Figure 1A This is a plan view of the end face of the honeycomb structure according to an embodiment of the present invention.
[0066] Figure 1B yes Figure 1A The cross-sectional view of the honeycomb structure along line a-a' is shown.
[0067] Figure 1C It is used for explanation Figure 1A A diagram showing the location of the contact portion on one side of the honeycomb structure.
[0068] Figure 2A This is a plan view of the end face of another honeycomb structure involved in an embodiment of the present invention.
[0069] Figure 2B yes Figure 2A The cross-sectional view of the b-b' line of the honeycomb structure shown.
[0070] Figure 3 It is a specific example of a honeycomb structure having columnar honeycomb units of various shapes.
[0071] Figure 4A It is a cross-sectional view of a honeycomb structure with columnar honeycomb units having slits, parallel to the direction of cell extension.
[0072] Figure 4B yes Figure 4A The cross-sectional view of the c-c' line of the honeycomb structure shown.
[0073] Figure 5 The attached figure is a schematic illustration of a method for measuring the hardness of a blank using a hardness tester.
[0074] Figure 6 It is an enlarged view showing the shape and size of the front end of the hardness tester.
[0075] Figure 7 It is a chart showing the spring properties of the spring material used in a hardness tester. Detailed Implementation
[0076] The honeycomb structure of the present invention comprises a plurality of columnar honeycomb cells containing an adsorbent material capable of adsorbing greenhouse gases. The sides of the plurality of columnar honeycomb cells are arranged opposite each other, and at least a portion of the sides of the opposing columnar honeycomb cells is in direct or indirect contact. The contact portion occupies 0.6% to 92.0% of the side surface of a single columnar honeycomb cell. The lengths of the contact portions along the axial direction and in the direction orthogonal to the axial direction of the columnar honeycomb cell are both at least 2% of the length of the side surface of the columnar honeycomb cell. With this configuration, greenhouse gases flow between the sides of the opposing columnar honeycomb cells, and these sides can be effectively utilized for the adsorption of greenhouse gases, thus increasing the amount of greenhouse gases adsorbed. Furthermore, this honeycomb structure ensures strength.
[0077] Hereinafter, embodiments of the present invention will be specifically described with reference to the accompanying drawings. The present invention is not limited to the following embodiments, and it should be understood that solutions obtained by appropriate modifications or improvements to the following embodiments based on ordinary knowledge of those skilled in the art without departing from the spirit of the present invention also fall within the scope of the present invention.
[0078] (1. Honeycomb structure)
[0079] Figure 1A This is a plan view of the end face of the honeycomb structure according to an embodiment of the present invention. Figure 1B yes Figure 1A The cross-sectional view of the honeycomb structure along line a-a' (parallel to the direction of the compartment extension). Figure 1C It is used for explanation Figure 1A A diagram showing the location of the contact portion on one side of the honeycomb structure.
[0080] in addition, Figure 2A This is a plan view of the end face of another honeycomb structure involved in an embodiment of the present invention. Figure 2B yes Figure 2A The cross-sectional view of the b-b' line of the shown cellular structure (a cross-sectional view parallel to the direction of the cell extension).
[0081] The honeycomb structure comprises multiple columnar honeycomb units 100. It should be noted that... Figures 1A to 2B The example shown has four columnar cell units 100; however, the number of columnar cell units 100 is not particularly limited. The number of columnar cell units 100 can be, for example, 2 to 25.
[0082] Multiple columnar cell units 100 are configured such that their sides 102 face each other. Furthermore, at least a portion of the facing sides 102 of the multiple columnar cell units 100 are in direct or indirect contact. It should be noted that... Figure 1A and Figure 1B An example of at least a portion of the opposite sides 102 being in indirect contact. Figure 2A and Figure 2B This is an example where at least a portion of the opposing sides 102 are in direct contact. In the case where at least a portion of the opposing sides 102 are in indirect contact, a gasket 110 can be disposed between the opposing sides 102. By configuring the opposing sides 102 in such a way that at least a portion of them are in direct or indirect contact, a space for the flow of greenhouse gases can be formed between the opposing sides 102.
[0083] The contact portion 104 occupies 0.6 to 92.0% of one side 102, preferably 2.0 to 70.0%, and more preferably 3.0 to 30.0%. By controlling it to such a proportion, a space for the circulation of greenhouse gases can be formed between the opposing sides 102.
[0084] Here, the proportion occupied by the contact portion 104 on one side surface 102 refers to the area ratio of the contact portion 104 (the area of the portion in direct contact with the opposite side surface 102, and the area of the portion in contact with the pad 110) in the surface area of one side surface 102. Therefore, for example, Figure 1A and Figure 1B The contact portion 104 shown occupies a proportion of one side 102 of the honeycomb structure. Figure 1C The middle value represents the ratio of the area of the contact portion 104 to the total area of the side surface 102 and the contact portion 104.
[0085] The lengths L1, L2, L3, and L4 of the contact portions 104 in the axial direction X and the direction Y orthogonal to the axial direction X of the columnar honeycomb unit 100 are each more than 2% of the length of the side surface 102. That is, as shown in the figure... Figure 1C As shown, the lengths L1 and L2 of the contact portions 104 along the axial direction X of the columnar honeycomb unit 100 (which are the total lengths of the multiple contact portions 104 if there are multiple contact portions 104) are at least 2% of the length of the side edge H1 of the side surface 102 along the axial direction X, and the lengths L3 and L4 of the contact portions 104 along the direction Y orthogonal to the axial direction X of the columnar honeycomb unit 100 (which are the total lengths of the multiple contact portions 104 if there are multiple contact portions 104) are at least 2% of the length of the side edge H2 of the side surface 102 along the direction Y. By controlling these ranges, the mechanical strength of the honeycomb structure composed of multiple columnar honeycomb units 100 can be improved.
[0086] The lengths L3 and L4 of the contact portion 104 in the direction Y, which is orthogonal to the axial direction X, of the columnar honeycomb unit 100 are preferably less than 90% of the length of the side edge H2 of the side surface 102, more preferably less than 50%, and even more preferably less than 30%. By controlling it to such a range, it is possible to suppress the increase in pressure loss when greenhouse gases flow between the opposing sides 102.
[0087] The lengths L1 and L2 of the contact portion 104 along the axial direction X of the columnar honeycomb unit 100 are preferably 30% or less of the length of the side edge H1 of the side surface 102, more preferably 20% or less, and even more preferably 10% or less. By controlling it to such a range, since greenhouse gas can easily come into contact with the side surface 102, the amount of greenhouse gas adsorbed can be increased.
[0088] The position of the contact portion 104 in the direction Y, orthogonal to the axial direction X, of the columnar cell unit 100 is not particularly limited, and can be set at the end and / or center of edge H2. Similarly, the position of the contact portion 104 in the axial direction X of the columnar cell unit 100 is not particularly limited, and can be set at the end and / or center of edge H1. By providing the contact portion 104 at such positions, the mechanical strength of the cell structure composed of multiple columnar cell units 100 can be improved.
[0089] It should be noted that there is no particular limitation on the number of contact parts on each side H1 and H2; for example, they can be set to 1 to 5.
[0090] As described above, a pad 110 is provided where at least a portion of the opposing sides 102 are in indirect contact.
[0091] The thickness of the pad 110 is not particularly limited, but is preferably 0.2 to 10.0 mm, more preferably 0.4 to 4.0 mm. Within this range, the mechanical strength of the honeycomb structure composed of multiple columnar honeycomb units 100 can be improved and compactness can be achieved.
[0092] Here, the thickness of the pad 110 refers to the length of the pad 110 on the opposite side 102.
[0093] As for the pad 110, it is only necessary to maintain the space between the opposing sides 102. There are no particular limitations, and pads of various materials can be used. For example, the pad 110 can be made of elastic materials such as rubber, resin, ceramic, metal, etc.
[0094] From the viewpoint of providing the columnar honeycomb unit 100 with a buffering capacity against expansion and contraction caused by moisture or dryness, the pad 110 preferably has an appropriate hardness depending on its type. For example, if it is an elastic material such as rubber, its hardness is preferably 5 to 40 measured with a type A hardness tester (measured according to JIS K6253-3:2023), or 10 to 50 measured with an ASKER type C hardness tester (measured according to SRIS 0101:1968). Furthermore, if it is a resin, ceramic, metal, etc., its hardness is preferably 50 to 1000 Hv measured with a Vickers hardness tester. Specific examples of pads 110 that meet these conditions include: silicone adhesive materials, silicone rubber sheets, graphite sheets, gel sheets, ethylene propylene rubber, polyurethane foam, ceramic fiber pads, metal fiber pads, glass fiber pads, aluminum alloys, copper alloys, stainless steel magnesium alloys, titanium alloys, nickel alloys, steel, bronze alloys, etc.
[0095] Alternatively, the liner 110 can be made of a material containing components capable of adsorbing greenhouse gases. By making the liner 110 of such a material, greenhouse gases can also be adsorbed within the liner 110, thus increasing the amount of greenhouse gases adsorbed. Examples of such materials are not particularly limited and include, for example, amino compounds (e.g., solid organic compounds containing amino groups), zeolites, activated carbon, etc.
[0096] The pad 110 is preferably made of a material whose required load for 80% compression is less than 2000 kPa. By making the pad 110 of a material with such properties, the mechanical strength of the honeycomb structure composed of multiple columnar honeycomb units 100 is easily improved, and the positions of the multiple columnar honeycomb units 100 and the pad 110 in the honeycomb structure are less likely to deviate. Examples of materials with such properties include: foamed silicone, crystalline alumina fibers, EPDM (ethylene propylene rubber) foam, etc.
[0097] From the viewpoint of consistently ensuring the above-mentioned effects, the load required to compress the gasket 110 by 80% is preferably 1950 kPa or less, more preferably 1900 kPa. It should be noted that the lower limit of the load required to compress the gasket 110 by 80% is not particularly limited, and may be set to, for example, 100 kPa, 200 kPa or 300 kPa.
[0098] Here, the load required to compress the gasket 110 by 80% is calculated as follows. First, a test piece of 2mm × 2mm × arbitrary thickness is taken from the gasket 110. Next, under the conditions of 25°C, 50% relative humidity, and atmospheric pressure, a force gauge with a circular attachment of 10mm diameter is used until the test piece is compressed from its original thickness to 80%. The rebound force (N) at this point and the area (mm²) of the attachment are then calculated.2 Calculate the rebound force (N / mm). 2 The rebound force is converted to kPa units.
[0099] The pad 110 is preferably disposed in the honeycomb structure such that when the thickness in the uncompressed state (not disposed in the honeycomb structure) is 'a', and the thickness in the compressed state (disposed in the honeycomb structure) is 'b', a / b is 1.0 or higher and lower than 20.0. By disposing the pad 110 under such conditions, the mechanical strength of the honeycomb structure composed of multiple columnar honeycomb units 100 is easily improved, and the positions of the multiple columnar honeycomb units 100 and the pad 110 in the honeycomb structure are less likely to deviate, thereby suppressing their detachment during use. From the viewpoint of stably ensuring this effect, a / b is preferably 1.1 to 19.0.
[0100] Here, regarding the thickness of the pad 110 in its uncompressed state, the thickness of the pad 110 (the pad 110 prepared for use during the manufacturing stage) is measured from a sample taken from the honeycomb structure. The thickness is measured under atmospheric pressure at a temperature of 25°C and a relative humidity of 50%. Furthermore, the thickness of the pad 110 in its compressed state, disposed within the honeycomb structure, is measured at the center of the two end faces of the honeycomb structure (including the first end face 122 and the second end face 124 of the plurality of columnar honeycomb cells 100) along the direction of the outer periphery of the columnar honeycomb cells 100.
[0101] The pad 110 is preferably made of a material whose residual compressive strain is less than 10% after being compressed 80% in a non-compressed state and held for 24 hours, and then measured after 30 minutes. By using a material with such properties, the pad 110 can follow the contraction of the columnar cell 100, thus easily achieving a cushioning effect. Consequently, the positions of the multiple columnar cell 100 and the pad 110 in the cell structure are less likely to deviate, thus preventing them from falling off during use.
[0102] Here, the residual compressive strain of the gasket 110 can be measured according to JIS K6262:2013. Specifically, the solution is as follows: First, gasket 110 (the gasket 110 prepared for use during the manufacturing stage) is collected from the honeycomb structure and compressed by 80% (until it becomes 20% of its original thickness) under an atmosphere of 25°C, 50% relative humidity, and atmospheric pressure, and held for 24 hours. Next, the gasket 110 is released from the compressed state, and after standing for 30 minutes, the residual compressive strain is measured.
[0103] The pad 110 is preferably made of a material that requires a load of less than 2000 kPa to compress 80% at 100°C, and whose residual compressive strain is less than 10% after being compressed 80% and held for 24 hours in a non-compressible state (never before being placed in a honeycomb structure) and then measured after 30 minutes. In the recovery (adsorption) and removal processes of greenhouse gases such as CO2, the honeycomb structure is sometimes exposed to an environment heated to 100°C. Therefore, by ensuring that the pad 110 possesses the aforementioned characteristics at 100°C, the reduction in buffering effect can be suppressed, and the aforementioned effect can be stably achieved.
[0104] The heat resistance temperature of the gasket 110 is preferably 100°C or higher. As mentioned above, in the recovery (adsorption) and removal processes of greenhouse gases such as CO2, the honeycomb structure is sometimes exposed to an environment heated to 100°C. Therefore, by making the heat resistance temperature of the gasket 110 100°C or higher, the above-mentioned effect is achieved without the gasket 110 deteriorating.
[0105] Here, the heat resistance temperature of the gasket 110 is determined as follows. First, the gasket 110 is heated in a constant temperature bath at a specified temperature for 1 hour, and then cooled for 30 minutes. After that, it is observed whether the shape, color, and function of the gasket 110 remain unchanged compared to before it was placed in the constant temperature bath. The maximum value of the temperature at which no change is observed is set as the heat resistance temperature.
[0106] The opposing sides 102 and the pad 110 of the columnar honeycomb unit 100 are preferably bonded together. By bonding the sides 102 and the pad 110 together, it is possible to suppress the displacement of the pad 110 during use.
[0107] Regarding the bonding of side 102 and gasket 110, adhesives or similar bonding agents can be used. The gasket 110, which has adhesive properties, can be used for bonding. There are no particular limitations on the type of gasket 110; any gasket formed using an adhesive is acceptable.
[0108] The columnar honeycomb unit 100 has an outer peripheral wall 120 and a partition wall 128 disposed on the inner side of the outer peripheral wall 120 and dividing it into a plurality of compartments 126 extending from a first end face 122 to a second end face 124. The plurality of compartments 126 are arranged in parallel with each other. The columnar honeycomb unit 100 is a through-type unit where the two end faces (first end face 122 and second end face 124) of each compartment 126 are open. When gas (air) containing greenhouse gases flows in from the first end face 122 with the inlet of the plurality of compartments 126, the greenhouse gases are adsorbed during the passage through the plurality of compartments 126, and the gas with a reduced concentration of greenhouse gases flows out from the second end face 124 with the outlet of the plurality of compartments 126.
[0109] The shape of the columnar honeycomb unit 100 can be such that at least a portion of the opposing side surfaces 102 can directly or indirectly contact each other; there is no particular limitation. For example, the two end faces (first end face 122 and second end face 124) of the columnar honeycomb unit 100 can be shaped as polygons such as quadrilaterals and hexagons, ellipses, racetrack shapes, oblong shapes, or other irregular shapes. It will have features other than... Figures 1A to 2B Specific examples of honeycomb structures with columnar honeycomb units other than those shown are given in Figure 3 It should be explained that... Figure 3 This is a three-dimensional diagram of a honeycomb structure. Note that in this diagram, only the outline of the columnar honeycomb unit 100 is shown; compartments and other elements are omitted.
[0110] The shapes of the two end faces of the columnar honeycomb unit 100 can be set such that the central part of the side H2 is located in a position closer to the inside than the end. Figure 3 (Left image), the shape of the central part of side H2 located on the outer side compared to the end ( Figure 3 (The central image). Additionally, such as... Figure 3 As shown in the right figure, a columnar honeycomb unit 100 can be configured with different shapes for the two end faces and different sizes for the cross-sectional shape at the center between the two end faces.
[0111] The length of the cell 126 of the columnar cell unit 100 in the extending direction (from the first end face 122 to the second end face 124) is not particularly limited and can be appropriately set according to performance requirements. The relationship between the length of the cell 126 of the columnar cell unit 100 in the extending direction and the maximum diameter of each end face (referring to the maximum length of the diameter passing through the centroid of each end face of the columnar cell unit 100) is also not particularly limited. Therefore, the length of the cell 126 of the columnar cell unit 100 in the extending direction can be longer than the maximum diameter of each end face, or it can be shorter than the maximum diameter of each end face.
[0112] However, a larger length in the direction of the extension of the compartment 126 of the columnar honeycomb unit 100 can increase the amount of greenhouse gas adsorption. On the other hand, if it is too large, the pressure loss will be greater. Therefore, the length is preferably 20 to 350 mm, more preferably 30 to 300 mm, and even more preferably 50 to 250 mm.
[0113] The diameter (equivalent circle diameter) of each end face of the columnar honeycomb unit 100 is not particularly limited. The diameter of each end face of a typical columnar honeycomb unit 100 is 10 to 350 mm, preferably 30 to 300 mm, and more preferably 50 to 250 mm.
[0114] Regarding the columnar honeycomb unit 100, the outer peripheral wall 120 and the partition wall 128 can be made of a material containing an adsorbent material capable of adsorbing greenhouse gases, or the adsorbent material capable of adsorbing greenhouse gases can be supported on the surface of the outer peripheral wall 120 and the partition wall 128. By using such a columnar honeycomb unit 100, greenhouse gases can be adsorbed efficiently. In addition, since the columnar honeycomb unit 100, in which the outer peripheral wall 120 and the partition wall 128 are made of a material containing an adsorbent material capable of adsorbing greenhouse gases, is manufactured without a high-temperature firing process, CO2 generated during manufacturing can be reduced, and the amount of greenhouse gases adsorbed can also be increased.
[0115] When the outer peripheral wall 120 and the partition wall 128 are made of a material containing an adsorbent capable of adsorbing greenhouse gases, the outer peripheral wall 120 and the partition wall 128 may also contain an organic binder in addition to the adsorbent capable of adsorbing greenhouse gases. Furthermore, the outer peripheral wall 120 and the partition wall 128 may further contain an inorganic binder as needed. The adsorbent capable of adsorbing greenhouse gases, the organic binder, and the inorganic binder may each be contained individually, or two or more may be contained simultaneously.
[0116] There are no particular limitations on the adsorbent material capable of adsorbing greenhouse gases. For example, materials with groups selected from amino (-NH2, -NHR, -NRR' (R and R' represent organic groups)) and ammonium (-NRR'R") can be used. + (R, R' and R” represent organic groups) or more solid organic compounds.
[0117] This invention is not intended to be theoretically limited; however, a solid organic compound selected from amino and ammonium groups reacts with a greenhouse gas (e.g., CO2) to form a carbamate or bicarbonate, thereby adsorbing the greenhouse gas. Both organic and inorganic binders contribute to ensuring the strength of the honeycomb structure; however, organic binders also contribute to improved formability, while inorganic binders contribute to improved water resistance and crack suppression during drying. To ensure formability, water-soluble organic binders are preferred; however, if water-soluble organic binders are included in the honeycomb structure, water resistance is reduced. Therefore, adding a normally non-water-soluble inorganic binder to the honeycomb structure helps to suppress the reduction in water resistance.
[0118] In this specification, "non-water soluble" refers to the following property: 11g of the substance used as the test object is placed in 1L of water at 20°C and stirred at 500rpm for 30 minutes. The liquid part is then removed by filtration using filter paper 5-C as specified in JIS P3801-1995, and the solid part is dried. The mass at this point is 10g or more.
[0119] From the viewpoint of achieving a good balance between the adsorption performance of greenhouse gases, crack suppression during drying, and water resistance, in a preferred embodiment, the outer peripheral wall 120 and the partition wall 128 contain 30-96% by mass of a solid organic compound selected from amino and ammonium groups, the outer peripheral wall 120 and the partition wall 128 contain 0-30% by mass of an inorganic binder, and the outer peripheral wall 120 and the partition wall 128 contain 3-70% by mass of an organic binder. In a more preferred embodiment, the outer peripheral wall 120 and the partition wall 128 contain 35-94% by mass of a solid organic compound selected from amino and ammonium groups, the outer peripheral wall 120 and the partition wall 128 contain 0-25% by mass of an inorganic binder, and the outer peripheral wall 120 and the partition wall 128 contain 5-30% by mass of an organic binder. In a further preferred embodiment, the content of a solid organic compound selected from amino and ammonium groups in the outer peripheral wall 120 and the partition wall 128 is 40-90% by mass, the content of an inorganic binder in the outer peripheral wall 120 and the partition wall 128 is 0-20% by mass, and the content of an organic binder in the outer peripheral wall 120 and the partition wall 128 is 5-20% by mass.
[0120] The peripheral wall 120 and the partition wall 128 may contain components other than solid organic compounds, inorganic binders, and organic binders having one or more amino and ammonium groups. For example, the peripheral wall 120 and the partition wall 128 may contain surfactants, pore-forming materials, etc. However, in a typical embodiment, the total content of the solid organic compounds, inorganic binders, and organic binders having one or more amino and ammonium groups in the peripheral wall 120 and the partition wall 128 is 90% by mass or more. In a more typical embodiment, the total content of the solid organic compounds, inorganic binders, and organic binders having one or more amino and ammonium groups in the peripheral wall 120 and the partition wall 128 is 95% by mass or more. Furthermore, the total content of the solid organic compounds, inorganic binders, and organic binders having one or more amino and ammonium groups in the peripheral wall 120 and the partition wall 128 may also be set to 99% by mass or more.
[0121] From the viewpoint of water resistance, solid organic compounds having one or more groups selected from amino and ammonium groups are preferably non-water-soluble. Furthermore, solid organic compounds having one or more groups selected from amino and ammonium groups may have the following structures: -NH2, -NHR, -NRR', -NRR'R". +(R, R', and R” represent organic groups) or combinations of two or more of them. Among the amino and ammonium groups, it is particularly preferred to contain a primary amine (-NH2) as a functional group. Solid organic compounds having one or more of the amino and ammonium groups also preferably contain an aromatic ring.
[0122] Specific examples of solid organic compounds having one or more amino and ammonium groups include weakly basic anion exchange resins having amino groups and strongly basic anion exchange resins having ammonium groups. Therefore, for example, as solid organic compounds having one or more amino and ammonium groups, styrene-based divinylbenzene polymers (e.g., copolymers of styrene and divinylbenzene) having one or more amino and ammonium groups and acrylic copolymers (e.g., copolymers of one or both of acrylic acid or methacrylic acid and divinylbenzene) having amino groups can be used. Furthermore, as strongly basic anion exchange resins, OH-type, Cl-type, and HCO3-type resins can also be used; however, for applications involving the adsorption of carbon dioxide, the OH-type or HCO3-type resins are preferred.
[0123] From the viewpoint of adsorption performance of greenhouse gases, the exchange capacity of a weakly basic anion exchange resin is preferably 0.6 meq / mL or more, more preferably 1.0 meq / mL or more, and even more preferably 1.4 meq / mL or more. Furthermore, from the viewpoint of adsorption performance of greenhouse gases, the exchange capacity of a strongly basic anion exchange resin is preferably 0.6 meq / mL or more, more preferably 0.8 meq / mL or more, and even more preferably 1.0 meq / mL or more.
[0124] Here, regarding the exchange capacity of the weakly basic anion exchange resin, the tap method is used to determine the exchange capacity. 10 mL of the resin is treated with hydrochloric acid, excess hydrochloric acid is washed away with ethanol, and ammonia solution is then circulated. The amount of chloride ions flowing out at this point is then used to determine the exchange capacity. Similarly, regarding the exchange capacity of the strongly basic anion exchange resin, the tap method is used to determine the exchange capacity. 10 mL of the resin is treated with hydrochloric acid, excess hydrochloric acid is washed away with ethanol, and a sodium hydroxide aqueous solution is circulated. The amount of chloride ions flowing out at this point is then used to determine the exchange capacity.
[0125] Examples of organic adhesives include: methylcellulose, hydroxypropyl methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, polyvinyl alcohol, hydroxyethyl methylcellulose, polyvinyl acetal, polyethylene oxide, polyvinyl butyral, polybutadiene, methacrylate, acrylic, ethylcellulose, silicone, and polyolefins. In particular, by using water-soluble organic adhesives such as methylcellulose, hydroxypropyl methylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, carboxymethylcellulose, polyvinyl alcohol, hydroxyethyl methylcellulose, polyvinyl acetal, and polyethylene oxide, environmental impact, hazards from organic solvent vapors during drying, and manufacturing costs can be reduced.
[0126] As inorganic binders, one or more inorganic binders selected from fibrous and granular forms can be cited, with fibrous inorganic binders being preferred. Inorganic binders are generally water-insoluble, thus exhibiting an effect of improving the water resistance of the columnar honeycomb unit 100. Additionally, they exhibit an effect of inhibiting cracking during drying. Here, "fibrous" inorganic binder refers to an inorganic binder with an average aspect ratio of 3 or more. "Granular" inorganic binder refers to an inorganic binder with an average aspect ratio of less than 3. The average aspect ratio of the inorganic binder is calculated in the following order: A test piece of the honeycomb structure is cut to an appropriate size, placed in a crucible, and heated in an electric furnace at 500°C to remove organic matter. Next, the remaining inorganic binder is dispersed on a scanning electron microscope (SEM) stage, with the magnification matched to the inorganic binder so that 20 inorganic binder particles fall entirely within one field of view. The longest and shortest diameters of any 20 inorganic adhesives were measured, and the average length of the longest / shortest diameter ratio was taken as the average aspect ratio of the inorganic adhesive. The longest diameter of an inorganic adhesive is defined as the longest distance between two parallel lines enclosing the adhesive in a SEM image. The shortest diameter of an inorganic adhesive is defined as the shortest distance between two parallel lines enclosing the adhesive in a SEM image.
[0127] Specific examples of inorganic binders include one or more selected from clay, diatomaceous earth, layered clay minerals, montmorillonite, hydrotalcite, activated clay, acid clay, lithium montmorillonite, halloysite, palygorskite, silica, alumina, talc, chlorite, vermiculite, mica, illite, pyrophyllite, sericite, kaolin, sepiolite, boehmite, palygorskite, and bentonite.
[0128] The inorganic binder preferably contains one or more of the following: sepiolite, boehmite, bentonite, silica, kaolin, and talc; more preferably, it contains sepiolite.
[0129] Therefore, the total content of one or more selected from sepiolite, boehmite, bentonite, silica, kaolin, and talc in the outer peripheral wall 120 and the partition wall 128 is preferably 0-30% by mass, more preferably 0-25% by mass, and even more preferably 0-20% by mass. Furthermore, the content of sepiolite in the outer peripheral wall 120 and the partition wall 128 is preferably 0-30% by mass, more preferably 0-25% by mass, and even more preferably 0-20% by mass.
[0130] The thickness of the outer peripheral wall 120 is not particularly limited, but from the point of view of ensuring strength, it is preferably 0.1 to 4.0 mm, more preferably 0.2 to 3.0 mm, and even more preferably 0.3 to 2.5 mm.
[0131] It should be noted that, in this specification, the thickness of the outer peripheral wall 120 refers to the length in the normal direction of the outer peripheral surface of the columnar honeycomb unit 100 from the boundary of the outer peripheral wall 120 and the outermost peripheral compartment 126 or partition wall 128 in a cross section orthogonal to the direction in which the compartment 126 extends.
[0132] The thickness of the partition 128 is not particularly limited, but from the point of view of ensuring strength, it is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more.
[0133] Furthermore, from the viewpoint of suppressing pressure loss, the thickness of the partition 128 is preferably 50 to 600 μm, more preferably 80 to 550 μm, and even more preferably 100 to 500 μm.
[0134] It should be noted that, in this specification, the thickness of partition 128 is defined as the length of the portion of the line segment connecting the centroids of adjacent compartments 126 in a cross-section orthogonal to the direction in which the compartments 126 extend, passing through partition 128. Furthermore, the thickness of partition 128 refers to the average thickness of all partitions 128 in the columnar honeycomb unit 100.
[0135] The outer peripheral wall 120 and the partition wall 128 preferably have the same thickness. By configuring it in this way, the strength of the columnar honeycomb unit 100 can be ensured, and the increase in pressure loss can be suppressed and the amount of greenhouse gas adsorbed can be increased.
[0136] The total pore volume of the outer peripheral wall 120 and the partition wall 128 is not particularly limited, but is preferably 0.2 to 1.5 cm. 3 / g, more preferably 0.3 to 1.0 cm 3 / g. By controlling the total pore volume within this range, greenhouse gases can easily diffuse into the columnar honeycomb unit 100 through the fine pores of the outer peripheral wall 120 and the partition wall 128, thus increasing the adsorption capacity of greenhouse gases.
[0137] It should be noted that in this instruction manual, the total pore volume can be determined by mercury porosity meter according to JIS R1655:2003 using the mercury injection method.
[0138] The average pore size of the outer peripheral wall 120 and the partition wall 128 is not particularly limited, but is preferably 0.1 to 15.0 μm, more preferably 0.3 to 8.0 μm. By controlling the average pore size within this range, greenhouse gases can easily diffuse through the fine pores of the outer peripheral wall 120 and the partition wall 128 into the columnar honeycomb unit 100, thereby increasing the adsorption capacity of greenhouse gases.
[0139] It should be noted that in this instruction manual, the average pore size can be determined by mercury porosimeter according to JIS R1655:2003 using the mercury injection method.
[0140] The shape of the compartment 126 in the cross-section orthogonal to the direction in which the compartment 126 extends is not particularly limited, but is preferably quadrilateral, hexagonal, octagonal, circular, or a combination thereof. Among these, square and hexagonal are preferred. By setting the shape of the compartment 126 in this way, it is possible to suppress the increase in pressure loss when fluid flows through the columnar honeycomb unit 100.
[0141] The cell density (number of cells 126 per unit cross-sectional area) of the columnar honeycomb unit 100 is not particularly limited, but from the viewpoint of increasing the contact area with gas, 30 cells / cm² is preferred. 2 The above is more preferably 40 compartments / cm. 2 That's all. Furthermore, from the viewpoint of suppressing increased pressure loss, the preferred compartment density is 2000 compartments / cm³. 2 The following is more preferably 1200 compartments / cm 2 The following is a further preferred value: 900 compartments / cm² 2 the following.
[0142] In this specification, the cell density is calculated by dividing the number of cells 126 in the columnar honeycomb unit 100 by the area of one end face of the columnar honeycomb unit 100 other than the peripheral wall 120.
[0143] In the columnar honeycomb cell 100, slits may be provided on the opposite side 102. By providing slits, cracks in the columnar honeycomb cell 100 caused by stress resulting from the adsorption and desorption of greenhouse gases can be suppressed. In addition, greenhouse gases can easily flow between adjacent columnar honeycomb cells 100 through the slits, thus increasing the amount of greenhouse gases adsorbed.
[0144] Here, a cross-section of the honeycomb structure having columnar honeycomb units 100 with slits, parallel to the direction in which the compartments 126 extend, is shown. Figure 4AIn addition, Figure 4A The cross-sectional view of the c-c' line of the shown honeycomb structure (a cross-sectional view orthogonal to the direction of extension of compartment 126) is shown in Figure 4B .
[0145] Figure 4A and Figure 4B In the honeycomb structure shown, each of the opposite sides 102 has one slit 130. However, the number of slits 130 on the opposite sides 102 can be multiple.
[0146] Furthermore, the position of the slit 130 in the opposing side 102 is not particularly limited, but at least a portion of the slit 130 is preferably provided on the side 102 that does not overlap with the contact portion 104. This is because: if it is only provided on the side 102 that overlaps with the contact portion 104, the effect brought by the slit 130 cannot be guaranteed.
[0147] The depth L5 of the slit is 130. Figure 4B The length L6 shown is preferably less than 50% of the length between the side 102 with the slit 130 and the side 102 opposite to the side 102 with the slit 130. By providing a slit 130 of such depth, it is possible to achieve a balance between the strength of the honeycomb structure and the effects brought about by the slit 130 mentioned above.
[0148] Here, the depth L5 of the slit 130 refers to the length of the slit 130 in the direction orthogonal to the side 102. When the slit 130 and the compartment 126 become one at the deepest part of the slit 130, the depth L5 refers to the length up to the partition wall 128.
[0149] The shape of slit 130 is as follows Figure 4A and Figure 4B The shape shown can be straight, but it can also be curved. In addition, the direction in which the slit 130 extends in the opposite side 102 is not particularly limited. It can be the axial direction X of the columnar honeycomb unit 100 (the direction in which the compartment 126 extends), or it can be the direction Y orthogonal to the axial direction X.
[0150] The maximum width of the slit 130 can be adjusted appropriately according to the shape and number of the slits 130, and is not particularly limited. It is preferably 50 mm or less, and more preferably 5 to 15 mm. By controlling the maximum width of the slit 130 to such a range, the strength of the columnar honeycomb unit 100 can be ensured.
[0151] The proportion of the slit 130 occupying one side 102 of the columnar honeycomb unit 100 is preferably 20% or less, more preferably 5.0% to 15.0%. In addition, the combined proportion of the contact portion 10 and the slit 130 occupying one side 102 is preferably less than 100%, more preferably 3.0% to 70.0%. By controlling it to such a range, it is possible to stably balance the strength of the honeycomb structure with the aforementioned effects brought about by the slit 130.
[0152] (2. Methods for recovering and removing greenhouse gases)
[0153] According to embodiments of the present invention, a method for recovering and removing greenhouse gases using a honeycomb structure is provided.
[0154] Specifically, the greenhouse gas recovery method according to the embodiments of the present invention includes: circulating a gas containing greenhouse gases through a honeycomb structure; during the passage of the gas through multiple honeycomb structures, adsorbing the greenhouse gases in the gas using an adsorption material; and allowing the gas with a reduced greenhouse gas concentration to flow out of the honeycomb structure.
[0155] As a gas, it can be any gas containing greenhouse gases, especially CO2, without any particular limitation. Examples include: ambient air (external atmosphere and indoor air), factory exhaust gas, ship exhaust gas, and power plant exhaust gas.
[0156] In addition, the method for removing greenhouse gases according to the embodiments of the present invention includes: passing a removal gas through a honeycomb structure in which greenhouse gases are adsorbed, and removing greenhouse gases from the adsorbent material into the removal gas during the passage of the removal gas through the honeycomb structure.
[0157] Here, the gas used for removal is any gas capable of removing greenhouse gases; there are no particular limitations. For example, water vapor can be used. Water vapor is preferably at a high temperature of 100°C or higher (e.g., 120°C).
[0158] (3. Manufacturing method of honeycomb structure)
[0159] Hereinafter, preferred examples of the method for manufacturing a honeycomb structure according to embodiments of the present invention will be described.
[0160] The method for manufacturing a honeycomb structure according to the embodiments of the present invention includes: a step of fabricating a plurality of columnar honeycomb cells 100, and a step of arranging the side surfaces 102 of the plurality of columnar honeycomb cells 100 to face each other and to arrange them in such a way that at least a portion of the facing side surfaces 102 are in direct or indirect contact.
[0161] First, the manufacturing process of the columnar honeycomb unit 100 will be explained.
[0162] When the columnar honeycomb unit 100, which is equipped with an adsorbent material capable of adsorbing greenhouse gases, is supported on the surfaces of the outer peripheral wall 120 and the partition wall 128, it can be manufactured according to conventional methods. Specifically, after the columnar honeycomb unit carrier is manufactured according to conventional methods, a slurry containing an adsorbent material capable of adsorbing greenhouse gases is coated onto the carrier and dried, thereby manufacturing the columnar honeycomb unit 100.
[0163] On the other hand, when the outer peripheral wall 120 and the partition wall 128 are made of a columnar honeycomb unit 100 containing an adsorbent material capable of adsorbing greenhouse gases, the manufacturing method includes the following steps: Step A, mixing a molding raw material containing a solvent, an adsorbent material capable of adsorbing greenhouse gases, an organic binder and an inorganic binder to make a blank; and Step B, molding the blank into a columnar honeycomb unit 100.
[0164] (Process A)
[0165] In step A, molding raw materials containing solvent, adsorbent material capable of adsorbing greenhouse gases, organic binder, and inorganic binder are mixed to produce a blank. Examples of solvents (dispersion media) include water or mixtures of water and organic solvents such as alcohols; water is particularly preferred.
[0166] When using bead-shaped adsorbents as adsorbents, they are pulverized to a certain size using a ball mill or similar device and then mixed, which makes it easier to control the total pore volume and average pore size. The median particle size (D50) of the pulverized adsorbent, when the cumulative particle size distribution on a volume basis is determined by laser diffraction scattering, is preferably in the range of 1.0 to 30.0 μm.
[0167] From the viewpoint of achieving a good balance between CO2 adsorption performance, crack suppression during drying, and water resistance, in a preferred embodiment, the content of adsorbent material capable of adsorbing greenhouse gases (excluding solvent) in the molding raw material is 30-96% by mass, the content of inorganic binder (excluding solvent) in the molding raw material is 0-30% by mass, and the content of organic binder (excluding solvent) in the molding raw material is 3-70% by mass. In a more preferred embodiment, the content of adsorbent material capable of adsorbing greenhouse gases (excluding solvent) in the molding raw material is 35-94% by mass, the content of inorganic binder (excluding solvent) in the molding raw material is 0-25% by mass, and the content of organic binder (excluding solvent) in the molding raw material is 5-30% by mass. In a further preferred embodiment, the content of adsorbent material capable of adsorbing greenhouse gases (excluding solvent) in the molding raw material is 40-90% by mass, the content of inorganic binder (excluding solvent) in the molding raw material is 0-20% by mass, and the content of organic binder (excluding solvent) in the molding raw material is 5-20% by mass.
[0168] The solvent content in the molding raw material is determined in a manner that produces a blank hardness suitable for extrusion. The blank hardness is preferably in the range of 14–26 mm, more preferably 15–25 mm, and even more preferably 16–24 mm. Here, in this specification, the blank hardness is determined using the following method. Figure 5 The attached diagram schematically illustrates the method for measuring the hardness of a billet using a hardness tester. (a) is an overall view of the hardness tester, (b) shows the measurement state when the billet is soft, and (c) shows the measurement state when the billet is relatively hard. Additionally, Figure 6 This is an enlarged view showing the shape and dimensions of the front end of the hardness tester. The conical front end 4 and the support portion 3 are connected by a spring material 2, and they are housed within a cylindrical sheath portion 5, thus forming the hardness tester 1. Figure 5 (a) in the middle. Figure 7This is a graph showing the spring properties of the spring material 2 used in the hardness tester 1. During the hardness measurement of the blank, firstly, a cubic sample of 20mm × 20mm × 20mm is collected from the blank. This sample is placed on a flat surface, and the front end 4 of the hardness tester 1 is vertically inserted into the blank 6 or 7 from above until the sheath 5 contacts the blank 6 or 7. Insertion is performed at a sheath speed of 1mm / s. Next, after 3 seconds from when the sheath 5 contacts the blank 6 or 7, the length (a1, a2) of the support 3 protruding above the sheath 5 is read. This value (mm) is defined as the hardness of the blank 6 or 7. Therefore, the larger the value, the higher and harder the hardness of the blank 6 or 7. In this specification, the average value of measurements taken at any two locations with different measurement positions is taken as the measured hardness value of the blank 6 or 7. It should be noted that L0, L1, and L2 represent the length of the spring material 2. Hardness testers that use this type of hardness measurement method are commercially available, such as the NGK hardness tester (model: NGK-01) manufactured by Nippon Kee Co., Ltd.
[0169] The mixing of the molding raw materials can be carried out using a known mixing machine, with the desired time required to achieve uniform distribution of each component in the billet.
[0170] (Process B)
[0171] In process B, the blank is formed into columnar honeycomb units 100.
[0172] Typically, in step B, the extrusion molding produces a columnar honeycomb unit 100, which has an outer peripheral wall 120 and partitions 128 disposed on the inner side of the outer peripheral wall 120 and dividing it into a plurality of compartments 126 extending from a first end face 122 to a second end face 124. During extrusion molding, a die with a desired overall shape, compartment shape, partition thickness, compartment density, etc., can be used.
[0173] The newly formed columnar honeycomb unit 100 contains solvent; therefore, it is preferable to remove the solvent through a drying process. The drying process can employ conventionally known drying methods such as hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, and freeze drying. Among these, hot air drying, microwave drying, dielectric drying, or a combination thereof are preferred for the purpose of rapidly and uniformly drying the entire formed body. From the viewpoint of suppressing the decomposition of the adsorbent material and organic binder during drying, it is preferable to dry the columnar honeycomb unit 100 in an atmospheric atmosphere at 50–150°C, more preferably in an atmospheric atmosphere at 60–140°C, and even more preferably in an atmospheric atmosphere at 70–130°C.
[0174] In addition, after the columnar honeycomb unit 100 is dried, the outer periphery can be ground as needed to be precision machined into the target shape, or the outer periphery can be coated with a ceramic material.
[0175] When a slit 130 is formed on the side of the columnar honeycomb unit 100, the method of forming the slit 130 is not particularly limited. For example, grinding, cutting, laser processing, water jet processing, electrical discharge machining (EDM) can be used. In addition, when the slit 130 is formed integrally in the direction of the extension of the compartment 126, a die having a portion corresponding to the slit 130 can be used.
[0176] Next, the sides 102 of the plurality of columnar honeycomb units 100 obtained above are arranged opposite each other, such that at least a portion of the opposite sides 102 are in direct or indirect contact. When the opposite sides 102 are arranged in an indirect contact manner, a pad 110 is placed at a predetermined position on the opposite sides 102. Alternatively, an adhesive can be used as the pad 110 as described above, and the pad 110 and the sides 102 can be bonded together using an adhesive.
[0177] (4. Greenhouse gas recovery device)
[0178] The greenhouse gas recovery device according to the embodiments of the present invention includes one or more of the above-described honeycomb structures. Because this greenhouse gas recovery device includes the above-described honeycomb structure, the amount of greenhouse gas adsorbed can be increased.
[0179] The greenhouse gas recovery device according to embodiments of the present invention may further include a housing for accommodating the honeycomb structure. Preferably, a pipe is connected to the housing for supplying and discharging the greenhouse gas and the detached gas. With such a structure, the recovery and detachment of greenhouse gases can be easily achieved.
[0180] Example
[0181] The present invention will now be described in detail by way of examples; however, the present invention is not limited to these examples.
[0182] [Experiment A (Examples 1-29 and Comparative Examples 1-15)]
[0183] <Fabrication of columnar honeycomb units (hereinafter referred to as "integrated articles") whose outer peripheral walls and partitions are made of materials containing adsorbent materials capable of adsorbing greenhouse gases: Examples 1-26, 28 and 29, Comparative Examples 1-14>
[0184] As an adsorbent material capable of adsorbing greenhouse gases, a commercially available, water-insoluble, weakly basic anion exchange resin (a styrene-based divinylbenzene polymer with a primary amine functional group and an exchange capacity of 2.0 meq / mL) was prepared. The adsorbent material was pulverized using a ball mill before mixing, and the median particle size (D50) was measured using laser diffraction scattering to determine the cumulative particle size distribution on a volume basis. The D50 values of the pulverized adsorbent materials used in each example and comparative example are shown in Tables 1-1 and 1-2.
[0185] As organic adhesive A, commercially available methylcellulose is prepared. As organic adhesive B, commercially available silicone is prepared.
[0186] Sepiolite is prepared for commercial use as an inorganic binder.
[0187] As a solvent, it is used to prepare industrial water.
[0188] As a backing, a commercially available silicone adhesive material (with a hardness of 20 on a type A hardness tester after curing) is used.
[0189] An adsorbent material capable of adsorbing greenhouse gases (hereinafter referred to as "adsorbent material"), an organic binder, an inorganic binder, and a solvent are combined to obtain a molding raw material. It should be noted that the contents of the adsorbent material, the organic binder (excluding the solvent), and the inorganic binder (excluding the solvent) in the molding raw material are shown in Tables 1-1 and 1-2. Furthermore, the amount of solvent is adjusted so that the hardness of the blank reaches 17 mm when measured using an NGK hardness tester (model: NGK-01) manufactured by Nippon Insulator Co., Ltd. Next, the molding raw material is mixed in a vacuum ply mill for 30 minutes to produce a blank.
[0190] Next, the obtained preform is shaped using an extrusion molding machine with a specified die structure to obtain quadrangular prism-shaped honeycomb units with quadrilateral cells in a cross-section perpendicular to the direction of cell extension. After high-frequency dielectric drying, the obtained quadrangular prism-shaped honeycomb units are dried in an atmospheric atmosphere at 100°C for 2 minutes using a microwave dryer, and the two end faces are cut off by a specified amount. In the obtained quadrangular prism-shaped honeycomb units, the end faces are square, with one side length of 120 mm and a length of 150 mm in the direction of cell extension. Furthermore, the cell density in the quadrangular prism-shaped honeycomb units is 46.5 cells / cm³. 2 (300 compartments / in 2 The thickness of the partition wall is 203 μm (8 mil). The thickness of the outer peripheral wall, the total pore volume of the outer peripheral wall and the partition wall, and the average pore diameter are shown in Tables 1-1 and 1-2. The total pore volume and average pore diameter were determined according to the method described above.
[0191] Regarding the quadrangular prism-shaped honeycomb cells used in Examples 28 and 29, when fabricating the honeycomb structure, slits are formed on the sides that are positioned opposite to other quadrangular prism-shaped honeycomb cells.
[0192] For the quadrangular prism-shaped honeycomb cell, a diamond tool is used to form slits extending along the axial direction of the prism-shaped honeycomb cell. In the quadrangular prism-shaped honeycomb cell used in Example 28, the slit depth is set to 5% of the length between the side with the slit and the side opposite to the side with the slit, the proportion of the slit occupying one side is set to 5%, and the maximum width of the slit is set to 5 mm. Furthermore, in the quadrangular prism-shaped honeycomb cell used in Example 29, the slit depth is set to 49% of the length between the side with the slit and the side opposite to the side with the slit, the proportion of the slit occupying one side is set to 19%, and the maximum width of the slit is set to 50 mm.
[0193] Next, prepare multiple obtained quadrangular prism-shaped honeycomb units, aligning their sides against each other. Place pads at designated positions on the opposing sides and assemble them to create a honeycomb structure. At this point, adjust the position and size of the pads to control the following proportions: the proportion of the contact portion on one side (hereinafter referred to as the "overall contact portion proportion"), the length of the contact portion along the X-axis of the quadrangular prism-shaped honeycomb unit (hereinafter referred to as the "axial contact portion length"), the ratio of the axial contact portion length to the length of the side edge H1 along the X-axis (hereinafter referred to as the "axial contact portion proportion"), the length of the contact portion along the Y-axis of the quadrangular prism-shaped honeycomb unit (hereinafter referred to as the "orthogonal direction contact portion length"), and the ratio of the length of the orthogonal direction contact portion to the length of the side edge H2 along the Y-axis (hereinafter referred to as the "orthogonal direction contact portion proportion") to the values shown in Tables 2-1 and 2-2. Here, when calculating the pad thickness based on the honeycomb structure, measure at least one point on the end face of the honeycomb structure using calipers, and average all measured values as the result. Alternatively, by determining the contact lengths in each direction based on the honeycomb structure, an X-ray CT scan can be performed on the honeycomb structure, and the contact lengths in each direction can be determined from the obtained X-ray CT images. Alternatively, the honeycomb structure can be decomposed to determine the padding thickness and the contact lengths in each direction.
[0194] It should be noted that in Tables 2-1 and 2-2, "number of groups" refers to, for example, in the case of 3×3, a total of 9 quadrangular prism honeycomb units, consisting of 3 quadrangular prism honeycomb units arranged horizontally with spacers and 3 quadrangular prism honeycomb units arranged vertically with spacers. Furthermore, "axial contact position" refers to the position of the contact portion on the side edge H1 along the axial X direction of the quadrangular prism honeycomb unit. "Overall" refers to the state where the contact portion is located entirely on edge H1; "both ends" refers to the state where the contact portion is located at both ends of edge H1; "inlet side" refers to the state where the contact portion is located at the gas inflow end of edge H1; "outlet side" refers to the state where the contact portion is located at the gas outflow end of edge H1; and "center" refers to the state where the contact portion is located at the center of edge H1. Similarly, "orthogonal contact position" refers to the position of the contact part in the side edge H2 of the quadrangular prism honeycomb unit in the direction Y orthogonal to the axial direction X. "whole" refers to the state in which the contact part is located in the whole of edge H2. "both ends" refers to the state in which the contact part is located at both ends of edge H2. "center" refers to the state in which the contact part is located in the center of edge H2.
[0195] <Preparation of columnar honeycomb cells (hereinafter referred to as "coatings") on the surface of the outer peripheral wall and partition walls carrying adsorbent material capable of adsorbing greenhouse gases: Example 27 and Comparative Example 15>
[0196] Alumina, aluminum hydroxide, kaolin, talc, and silica were used as raw materials for cordierite petrochemicals. 10 parts by weight of a pore-forming material, 20 parts by weight of a dispersion medium, 1 part by weight of an organic binder, and 0.5 parts by weight of a dispersant were added to 100 parts by weight of this cordierite petrochemical raw material, and the mixture was stirred and kneaded to prepare a preform. Water was used as the dispersion medium, coke with an average particle size of 15 μm was used as the pore-forming material, hydroxypropyl methylcellulose was used as the organic binder, and ethylene glycol was used as the dispersant. Next, the obtained preform was formed using an extrusion molding machine with a specified die structure to obtain a quadrangular prism-shaped honeycomb unit with quadrangular compartments in a cross-section perpendicular to the direction of compartment extension. The obtained quadrangular prism-shaped honeycomb unit was dried in a microwave dryer, then dried in a hot air dryer, and finally, the two end faces of the honeycomb unit were cut off and adjusted to the specified dimensions. Next, the obtained quadrangular prism-shaped honeycomb unit was degreased in the atmosphere at 200-1000°C for 3 hours, and then fired in an Ar atmosphere at 1420°C for 2 hours.
[0197] Next, a slurry containing the same adsorbent material and ethyl cellulose as described above is prepared and coated onto the partition walls and outer peripheral walls, then dried to obtain a tetragonal prism-shaped honeycomb unit. In the obtained tetragonal prism-shaped honeycomb unit, the end faces are square, with one side length of 120 mm and the length in the direction of cell extension of 150 mm. Furthermore, the cell density in the tetragonal prism-shaped honeycomb unit is 46.5 cells / cm³.2 (300 compartments / in 2 The thickness of the partition wall is 635 μm (25 mil). The thickness of the outer peripheral wall and the content of adsorbent material in the quadrangular prism honeycomb unit (the loading ratio of adsorbent material in the quadrangular prism honeycomb unit) are shown in Table 1-2.
[0198] Next, prepare multiple obtained quadrangular prism-shaped honeycomb units, align the sides of the quadrangular prism-shaped honeycomb units with each other, place pads at specified positions on the opposing sides, and assemble them to create a honeycomb structure. At this time, adjust the position and size of the pads to control the overall contact ratio, axial contact length, axial contact ratio, orthogonal contact length, and orthogonal contact ratio to the values shown in Table 2-2.
[0199] [Table 1-1]
[0200]
[0201] [Table 1-2]
[0202]
[0203] [Table 2-1]
[0204]
[0205] [Table 2-2]
[0206]
[0207] The honeycomb structure obtained above is evaluated as follows.
[0208] <CO2 adsorption capacity and CO2 adsorption rate>
[0209] After the honeycomb structure was placed in a retainer and configured within a sealed container, CO2 sensors were installed at both the inlet and outlet sides of the honeycomb structure. Next, as a pretreatment, nitrogen gas heated to 90°C–100°C was circulated through the honeycomb structure at a flow rate of 500 L / min until the CO2 concentration at the outlet side reached 0 ppm. Heating was then stopped while nitrogen gas continued to circulate until the temperature dropped to 25°C (room temperature). Once 25°C was reached, air at 25°C was circulated at a flow rate of 4900 L / min, and the CO2 adsorption capacity until saturation was measured. The saturated CO2 adsorption capacity was divided by the mass of the honeycomb structure to determine the CO2 adsorption capacity per unit mass of the honeycomb structure.
[0210] It should be noted that the nitrogen and air flow rates described above apply to a 3×3 honeycomb structure. For a 20×20 honeycomb structure, the nitrogen flow rate is changed to 22,500 L / min and the air flow rate to 218,000 L / min. Furthermore, for a 2×2 honeycomb structure, the nitrogen flow rate is changed to 225 L / min and the air flow rate to 218 L / min.
[0211] The evaluation of CO2 adsorption capacity is affected by the number of adsorption groups, the content of adsorption materials, the total pore volume, the average pore size, and the type of tetragonal prism honeycomb units. Therefore, the following comparison benchmark is determined.
[0212] First, honeycomb structures with the same number of adsorption materials, total pore volume, and average pore size were compared. For example, in the case of a 3×3 honeycomb structure, the CO2 adsorption capacity of Comparative Example 1 was used as the comparison benchmark; in the case of a 20×20 honeycomb structure, the CO2 adsorption capacity of Comparative Example 11 was used as the comparison benchmark; and in the case of a 2×2 honeycomb structure, the CO2 adsorption capacity of Comparative Example 12 was used as the comparison benchmark.
[0213] The honeycomb structure with an adsorption material content of 96% was compared with the CO2 adsorption capacity of Comparative Example 13.
[0214] The adsorption capacity of the honeycomb structure with an adsorption material content of 30% and different total pore volumes and average pore sizes was compared with that of Comparative Example 14 as the benchmark.
[0215] The quadrangular prism-shaped honeycomb unit is the honeycomb structure of the coating, with the CO2 adsorption amount of Comparative Example 15 as the comparison benchmark.
[0216] In addition, the CO2 adsorption capacity is evaluated using the following evaluation scores relative to the above-mentioned comparison benchmark.
[0217] Evaluation score 0: This is the benchmark, or the CO2 adsorption amount is the same as or less than the benchmark.
[0218] Evaluation score 1: The increase in CO2 adsorption is greater than 0% and less than 5% relative to the benchmark.
[0219] Evaluation score 2: The increase in CO2 adsorption is greater than 5% but less than 10% relative to the benchmark.
[0220] Evaluation score 3: The increase in CO2 adsorption is greater than 10% but less than 15% relative to the benchmark.
[0221] Evaluation score 4: The increase in CO2 adsorption is greater than 15% but less than 20% relative to the benchmark.
[0222] Evaluation score 5: Compared with the benchmark, the increase in CO2 adsorption is more than 20%.
[0223] In addition, the amount of CO2 adsorbed per minute [mol / kg / min] is calculated from the amount of CO2 adsorbed after 20 minutes from the start of CO2 adsorption, and this value is calculated as the "CO2 adsorption rate".
[0224] The evaluation of CO2 adsorption rate follows the same comparison criteria as the evaluation of CO2 adsorption capacity. Furthermore, the evaluation of CO2 adsorption rate is based on the following evaluation scores relative to the aforementioned comparison criteria.
[0225] Evaluation score 0: It is the benchmark, or the CO2 adsorption rate is the same as or slower than the benchmark.
[0226] Evaluation score 1: The increase in CO2 adsorption rate relative to the benchmark is greater than 0% and less than 2.5%.
[0227] Evaluation Score 2: The increase in CO2 adsorption rate relative to the benchmark is greater than 2.5% but less than 5.0%.
[0228] Evaluation score 3: The increase in CO2 adsorption rate relative to the benchmark is greater than 5.0% but less than 7.5%.
[0229] Evaluation score 4: The increase in CO2 adsorption rate relative to the benchmark is greater than 7.5% but less than 10%.
[0230] Evaluation score 5: The increase in CO2 adsorption rate is more than 10% compared to the benchmark.
[0231] <Pressure Loss>
[0232] After the honeycomb structure is placed in the retainer and configured in a sealed container, pressure sensors are installed on the inlet and outlet sides of the honeycomb structure, respectively. Next, air at 25°C is circulated at a flow rate of 3000 kg / h, and the pressure difference between the inflow and outflow sides is taken as the result of pressure loss.
[0233] It should be noted that the airflow rate described above applies to a 3×3 honeycomb structure. For a 20×20 honeycomb structure, the airflow rate is changed to 12440 L / h. Furthermore, for a 2×2 honeycomb structure, the airflow rate is changed to 124 L / h.
[0234] The evaluation of pressure loss is based on the same comparison criteria as the evaluation of CO2 adsorption capacity, etc. Furthermore, the evaluation of pressure loss is conducted using the following evaluation scores relative to the aforementioned comparison criteria.
[0235] Evaluation score 0: It is the benchmark, or the pressure difference is the same as or greater than the benchmark.
[0236] Evaluation score 1: The reduction in pressure difference is greater than 0% and less than 1.5% relative to the benchmark.
[0237] Evaluation Score 2: The pressure difference reduction rate is greater than 1.5% and less than 3.0% relative to the benchmark.
[0238] Evaluation score 3: The pressure difference reduction rate is greater than 3.0% and less than 4.5% relative to the benchmark.
[0239] Evaluation score 4: The pressure difference reduction rate is greater than 4.5% and less than 6.0% relative to the benchmark.
[0240] Evaluation score 5: The pressure difference reduction rate is greater than 6.0% and less than 7.5% relative to the benchmark.
[0241] Evaluation score 6: The pressure difference reduction rate is greater than 7.5% and less than 9.0% relative to the benchmark.
[0242] Evaluation score 7: The pressure difference reduction rate is greater than 9.0% and less than 11.5% relative to the benchmark.
[0243] Evaluation score 8: The pressure difference reduction rate is greater than 11.5% and less than 13.5% relative to the benchmark.
[0244] Evaluation score 9: The pressure difference reduction rate is greater than 13.5% and less than 15.0% relative to the benchmark.
[0245] Evaluation score 10: The pressure difference is reduced by more than 15.0% relative to the benchmark.
[0246] <Mechanical Strength>
[0247] A weight of specified mass (the width of the weight is the same as the width of the honeycomb structure) is placed on the honeycomb structure and left for approximately 30 seconds. The same weight is then placed on the other three faces to check for cracks or other damage. The weight is increased in increments of 2 kg, starting from 2 kg, and this process is repeated to determine the mechanical strength. The mass of the weight before cracks or other damage are detected is taken as the result of the mechanical strength measurement.
[0248] Mechanical strength is evaluated using the following evaluation scores.
[0249] Evaluation score 0: Mechanical strength is below 4kg.
[0250] Evaluation score 1: Mechanical strength is 6-10 kg.
[0251] Evaluation score 2: Mechanical strength is 12-16 kg.
[0252] Evaluation score 3: Mechanical strength is 18-22 kg.
[0253] Evaluation score 4: Mechanical strength is 24-28 kg.
[0254] Evaluation score 5: Mechanical strength is above 30kg.
[0255] The evaluation results are shown in Tables 3-1 and 3-2.
[0256] [Table 3-1]
[0257]
[0258] [Table 3-2]
[0259]
[0260] As shown in Tables 3-1 and 3-2, in the honeycomb structures of Examples 1 to 29, where the overall contact portion ratio is 0.6% to 92.0% and the axial contact portion ratio and orthogonal direction contact portion ratio are 2% or more, the results for CO2 adsorption capacity, CO2 adsorption rate, pressure loss and mechanical strength are all good.
[0261] In contrast, in the honeycomb structures of Comparative Examples 1 to 15, at least one of the overall contact portion ratio, the axial contact portion ratio, and the orthogonal direction contact portion ratio does not meet the specified range. Therefore, at least one of the CO2 adsorption amount, CO2 adsorption rate, and mechanical strength is insufficient.
[0262] [Experiment B (Examples 30-44)]
[0263] Multiple quadrangular prism-shaped honeycomb units, fabricated in the same manner as in Example 1, are prepared. The sides of the quadrangular prism-shaped honeycomb units are placed opposite each other, and pads are placed at predetermined positions on the opposite sides. The units are then assembled to create a honeycomb structure. At this time, the number of units, overall contact ratio, axial contact position, axial contact length, axial contact ratio, orthogonal contact position, orthogonal contact length, orthogonal contact ratio, and pad thickness are the same as in Example 1, except for the type of pad. Table 4 shows the characteristics of the pads used. Specifically, the load required for 80% compression of the pad (hereinafter referred to as "required load at 80% compression"), the a / b ratio when the thickness in the uncompressed state (not placed in the honeycomb structure) is set as a, and the thickness in the compressed state (placed in the honeycomb structure) is set as b (hereinafter referred to as "a / b"), the residual compression strain (hereinafter referred to as "residual compression strain") measured after 30 minutes following 80% compression from the uncompressed state (not placed in the honeycomb structure) and holding for 24 hours, and the heat resistance temperature of the pad (hereinafter referred to as "heat resistance temperature"). It should be noted that the required load, a / b, residual compressive strain, and heat resistance temperature at 80% compression are obtained using the methods described above.
[0264] [Table 4]
[0265]
[0266] The following evaluation is performed on the honeycomb structure obtained above.
[0267] <Mechanical Strength>
[0268] The same evaluation method as Experiment A was used.
[0269] <Maintaining Performance>
[0270] After the honeycomb structure is placed in a retainer and disposed in a sealed container, air at 25°C is circulated at 3000 kg / h for 24 hours. The positions of the quadrangular prism honeycomb cells and the padding constituting the honeycomb structure are evaluated to determine whether they have moved from their initial positions. This evaluation is conducted using the following evaluation scores.
[0271] Evaluation score 0: The quadrangular prism honeycomb unit, the pad, or both move from their initial position and detach from the retainer.
[0272] Evaluation score 1: The quadrangular prism honeycomb unit, the pad, or both moved from the initial position; however, no self-holding component detached.
[0273] Evaluation score 2: The quadrangular prism honeycomb cells, pads, or both did not move from their initial positions.
[0274] <Buffering performance>
[0275] After the honeycomb structure was placed in a retainer and disposed in a sealed container, a water-containing expansion-drying-shrinkage cycle was performed 12 times (totaling 24 hours) by alternately circulating 3000 kg / h of 100°C water vapor and 3000 kg / h of 25°C air for 1 hour each. The changes in the quadrangular prism-shaped honeycomb units constituting the honeycomb structure from their initial state and the presence of cracks were then evaluated. This evaluation was conducted using the following evaluation scores.
[0276] Evaluation score 0: Due to deformation and cracking from the initial state, the quadrangular prism honeycomb unit is unable to maintain its own structure, and the honeycomb structure collapses.
[0277] Evaluation score 1: Deformation and cracking occurred in the quadrangular prism-shaped honeycomb units from their initial state; however, the honeycomb structure did not collapse.
[0278] Evaluation score 2: The quadrangular prism honeycomb unit deformed from its initial state, but no cracks were generated.
[0279] Evaluation score 3: No deformation or cracks occurred in the quadrangular prism honeycomb unit from its initial state.
[0280] The evaluation results are shown in Table 5.
[0281] [Table 5]
[0282]
[0283] As shown in Table 5, if a / b is less than 1.0, a trend of decreasing performance is observed. Furthermore, if a / b exceeds 20.0, the compressive residual strain is greater than 10%, and the heat resistance temperature is below 100°C, a trend of decreasing mechanical strength and cushioning performance is observed.
[0284] Explanation of reference numerals in the attached figures
[0285] 1: Hardness tester
[0286] 2: Spring material
[0287] 3: Support section
[0288] 4: Front end
[0289] 5: Sheath
[0290] 6, 7: Billet
[0291] a1, a2: Prominent length
[0292] 100: Columnar honeycomb unit
[0293] 102: Side View
[0294] 104: Contact Department
[0295] 110: Padding
[0296] 120: Peripheral wall
[0297] 122: First end face
[0298] 124: Second end face
[0299] 126: Compartment
[0300] 128: Next door
[0301] 130: Slit
Claims
1. A honeycomb structure comprising multiple columnar honeycomb units containing an adsorbent material capable of adsorbing greenhouse gases. The honeycomb structure is characterized in that... The columnar honeycomb units are arranged such that their sides face each other, and at least a portion of the facing sides are in direct or indirect contact. The contact portion occupies 0.6% to 92.0% of one of the said sides. The lengths of the contact portions in the axial direction and in the direction orthogonal to the axial direction of the columnar honeycomb unit are both more than 2% of the length of the side edge.
2. The honeycomb structure according to claim 1, characterized in that, At least a portion of the opposite sides are in contact with each other through a pad.
3. The honeycomb structure according to claim 2, characterized in that, The thickness of the liner is 0.2 to 10.0 mm.
4. The honeycomb structure according to any one of claims 1 to 3, characterized in that, The length of the contact portion of the columnar honeycomb unit in the direction orthogonal to the axial direction is less than 90% of the length of the side edge.
5. The honeycomb structure according to claim 4, characterized in that, The contact portion is located at the end and / or center of the side edge of the columnar honeycomb unit in a direction orthogonal to the axial direction.
6. The honeycomb structure according to any one of claims 1 to 3, characterized in that, The length of the contact portion along the axial direction of the columnar honeycomb unit is less than 30% of the length of the side edge.
7. The honeycomb structure according to claim 6, characterized in that, The contact portion is located at the end and / or center of the side edge of the columnar honeycomb cell along the axial direction.
8. The honeycomb structure according to any one of claims 1 to 3, characterized in that, A slit is provided on the opposite side.
9. The honeycomb structure according to claim 8, characterized in that, At least a portion of the slit is disposed on the side surface that does not overlap with the contact portion. The depth of the slit is less than 50% of the length between the side with which the slit is formed and the side opposite to the side with which the slit is formed. The slit occupies less than 20% of one of the sides, and, The combined proportion of the contact portion and the slit on one of the sides is less than 100%.
10. The honeycomb structure according to claim 9, characterized in that, The maximum width of the slit is less than 50 mm.
11. The honeycomb structure according to any one of claims 1 to 3, characterized in that, The columnar honeycomb unit has an outer peripheral wall and a partition wall, the partition wall being disposed on the inner side of the outer peripheral wall and dividing it into multiple compartments extending from a first end face to a second end face.
12. The honeycomb structure according to claim 11, characterized in that, The total pore volume of the outer peripheral wall and the partition wall is 0.2–1.5 cm. 3 / g.
13. The honeycomb structure according to claim 11, characterized in that, The average pore size of the outer peripheral wall and the partition wall is 0.1 to 15.0 μm.
14. The honeycomb structure according to claim 11, characterized in that, The thickness of the outer peripheral wall is 0.1 to 4.0 mm.
15. The honeycomb structure according to claim 11, characterized in that, The outer peripheral wall and the partition wall have the same thickness.
16. The honeycomb structure according to claim 11, characterized in that, The outer peripheral wall and the partition wall are made of a material containing the adsorbent material.
17. The honeycomb structure according to claim 11, characterized in that, The adsorbent material is supported on the surface of the outer peripheral wall and the partition wall.
18. The honeycomb structure according to any one of claims 1 to 3, characterized in that, The content of the adsorbent material in the columnar honeycomb unit is 30-96% by mass.
19. The honeycomb structure according to claim 2, characterized in that, The gasket has adhesive properties.
20. The honeycomb structure according to claim 2, characterized in that, The liner is made of a material containing components capable of adsorbing greenhouse gases.
21. The honeycomb structure according to claim 2, characterized in that, The liner is made of a material that requires a load of less than 2000 kPa to compress 80%.
22. The honeycomb structure according to claim 2, characterized in that, The pad is disposed in the cell structure such that when the thickness in the uncompressed state not disposed in the cell structure is set as a, and the thickness in the compressed state disposed in the cell structure is set as b, a / b is greater than 1.0 and less than 20.
0.
23. The honeycomb structure according to claim 2, characterized in that, The liner is made of a material whose residual compressive strain is less than 10% after being compressed 80% from its uncompressed state (not configured in the honeycomb structure) and held for 24 hours, followed by a 30-minute interval.
24. The honeycomb structure according to claim 2, characterized in that, The heat resistance temperature of the gasket is above 100°C.
Citation Information
Patent Citations
CO2 RECOVERY ARTICLE AND MANUFACTURING METHOD THEREOF
JP2018538137A